Ordinance No. 317: An Ordinance Concerning Offenses and Disorderly Conduct, THE DAILY ASTORIAN, Feb. 22, 1879, at 3, § 2 (Astoria, OR) - (:unkn) unknown (General Publisher, 1879)
That any person or persons who shall fire any pistol, gun or rifle or any other kind of fire-arms within the corporate limits of the city, shall on conviction thereof before the Police court, be fined not less than five nor more than fifty dollars
--
Keywords: DISCHARGE